Uma via para a prosperidade: a estrada de Baturité e o Ceará (1836-1972) - Soares, Igor de Menezes (2015)
Throughout the development of this research, we find constant references to fertility unusual regarding the Baturité saw and repeated observations on the need for a road shooting that would link the capital of Ceará province, Fortaleza, to Baturité, located in foot of the Baturité mountains.We found several individuals who were willing to provide considerations on the aforementioned mountains as well as on the Baturité road, as the said land on which we are dedicated to researching the course of this research has been called, among them politicians, naturalists, researchers, traders. We realized then that we had elements that related to construction of meanings that alluded to some of the province spaces as well as concrete actions that undoubtedly redefined the spatial organization of Ceara province. Thus, our attempts aimed to analyze and understand the meanings made about Baturité saw, considering it was very often exalted by his unusual uberdade and as an indispensable space in relation to the provincial economic prosperity, and seek understanding about the process opening and development of a public work considered the most relevant for the province, as was the Baturité road.